Ectodysplasin pathogenic variants affecting the furin‐cleavage site and unusual clinical features define X‐linked hypohidrotic ectodermal dysplasia in India. Issue 3 (4th December 2021) - Chaudhary, Ajay Kumar; Gholse, Aishwarya; Nagarajaram, Hampapathalu Adimurthy; Dalal, Ashwin Bhikaji; Gupta, Neerja; Dutta, Atanu Kumar; Danda, Sumita; Gupta, Rekha; Sankar, Hariharan V.; Bhavani, Gandham SriLakshmi; Girisha, Katta M.; Phadke, Shubha Rao; et al.
Abstract: Hypohidrotic ectodermal dysplasia (HED) is a rare genetic disorder caused by mutational inactivation of a developmental pathway responsible for generation of tissues of ectodermal origin. The X‐linked form accounts for the majority of HED cases and is caused by Ectodysplasin ( EDA ) pathogenic variants. We performed a combined analysis of 29 X‐linked hypohidrotic ectodermal dysplasia (XLHED) families (including 12 from our previous studies). In addition to the classical triad of symptoms including loss (or reduction) of ectodermal structures, such as hair, teeth, and sweat glands, we detected additional HED‐related clinical features including facial dysmorphism and hyperpigmentation in several patients. Interestingly, global developmental delay was identified as an unusual clinical symptom in many patients. More importantly, we identified 22 causal pathogenic variants that included 15 missense, four small in‐dels, and one nonsense, splice site, and large deletion each. Interestingly, we detected 12 unique (India‐specific) pathogenic variants. Of the 29 XLHED families analyzed, 11 (38%) harbored pathogenic variant localized to the furin cleavage site. A comparison with HGMD revealed significant differences in the frequency of missense pathogenic variants; involvement of specific exons and/or protein domains and transition/transversion ratios. A significantly higher proportion of missense pathogenic variants (33%) localized to the EDA furin cleavage when compared to HGMD (7%), of which p.R155C, p.R156C, and p.R156H were detected in three families each. Therefore, the first comprehensive analysis of XLHED from India has revealed several unique features including unusual clinical symptoms and high frequency of furin cleavage site pathogenic variants.